Measured UV exposures of Ironman, sprint and Olympic-distance triathlon competitors - Downs, N. J.; Axelsen, T.; Parisi, A. V.; Schouten, A. V.; Dexter, A. R. (Atmosphere, 2020)
Triathletes present an extreme case of modelled behaviour in outdoor sport that favours enhanced exposure to solar ultraviolet radiation. This research presents personal solar ultraviolet exposures, measured using all-weather polysulphone film dosimeters, to triathletes during the distinct swimming, cycling and running stages of competitive Sprint, Olympic and Ironman events conducted within Australia and New Zealand. Measurements of exposure are made for each triathlon stage using film dosimeters fixed at a single site to the headwear of competing triathletes. Exposures are expressed relative to the local ambient and as absolute calibrated erythemally effective values across a total of eight triathlon courses (two Ironman, one half Ironman, one Olympic-distance, and four Sprint events). Competitor exposure results during training are also presented. Exposures range from between 0.2 to 6.8 SED/h (SED: standard erythema dose) depending upon the time of year, the local time of each event and cloud conditions. Cycle stage exposures can exceed 20 SED and represent the highest exposure fraction of any triathlon (average = 32%). The next highest stage exposure occurred during the swim (average = 28%), followed by the run (average = 26%). During an Ironman, personal competitor exposures exceed 30 SED, making triathlon a sporting discipline with potentially the highest personal ultraviolet exposure risk.